Quality assurance in Asia-Pacific universities : implementing massification in higher education - Neubauer, Deane E.; Gomes, Catherine (New York, NY : Springer International Publishing AG, 2017)
This edited volume examines the importance of quality issues in contemporary higher education systems in the Asia Pacific. Part Three extends the research of higher education quality assurance in Hawaii Pacific University (HPU) and the diverse international student body in the Australian higher education system.
Includes bibliographical references and index.
IQAC
TrimEducation
Keywords: Education, Higher -- Asia; Total quality management in higher education -- Asia; Universities and colleges -- Ratings and rankings -- Asia; Quality assurance -- Asia; Education, Higher